Board Level Employee Representation and Tax Avoidance in Europe - Sigurt Vitols (Accounting, Economics, and Law: A Convivium, 2021)
In part due to recent disclosures of large-scale tax evasion (e.g. Panama Papers), corporate tax avoidance has become a prominent public policy issue around the world. An increasing amount of research on this topic has focused on identifying the determinants of tax avoidance at the company and country level. Many newer studies examine differences in corporate governance as one of these determinants. However, this literature almost entirely neglects the role of board level employee representation (BLER), despite the fact that this form of `stakeholder governance' is widespread in Europe. This paper addresses this gap in the literature by examining the relationship between BLER and tax avoidance at the company level. Two mechanisms are identified through which BLER might influence corporate tax behavior: 1) reduction in agency costs through monitoring and 2) the voting power of workers as board members to enter into coalitions with management and/or shareholders. Based on a sample of 2343 European listed companies between 2012 and 2017, this paper shows that companies with BLER have a higher effective tax rate (ETR) than companies without workers on the board. The analysis suggests that the ability to form coalitions through voting power is a more significant channel for influencing tax behavior than the monitoring mechanism. The policy implications are that governments should consider `stakeholder governance' such as BLER as one measure supporting their efforts to combat tax avoidance.
Keywords: H26; J51; 330; tax avoidance; worker participation; co-determination; stakeholder governance